FORMATION OF STUDENTS’ COMMUNICATIVE SKILLS IN RUSSIAN LANGUAGE CLASSES - Akramova Nigora Yadullaevna; Sidirova Janar Umirbekovna (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
The article examines the issue of developing communication skills among students during Russian language classes. Communication skills include the ability to communicate effectively, listen, and express thoughts both orally and in written form. Special attention is given to various methods and techniques that can be applied during lessons to develop these skills, such as group tasks, dialogues, discussions, the use of games, and creative assignments. These methods contribute not only to speech development but also to the formation of students’ social competence.